Initial observational management of hydronephrosis in infants with reduced differential renal function and non-obstructive drainage parameters. Issue 5 (October 2022) - Hester, Austin G.; Krill, Aaron; Shalaby-Rana, Eglal; Rushton, H. Gil
Summary: Introduction: Hydronephrosis secondary to ureteropelvic junction (UPJ) obstruction is a common finding in infants with prenatally-diagnosed hydronephrosis and often results in pyeloplasty due to obstructive drainage parameters and/or renal function compromise. However, little is known regarding the natural history of hydronephrosis with reduced differential renal function (DRF) but non-obstructive drainage. Objective: We sought to explore our experience with initial observational management of these patients. Study design: A retrospective review of our institutional database of all diuretic MAG-3 renal scans obtained between 2000 and 2016 was performed. We included patients with antenatally-detected unilateral hydronephrosis ≥ SFU grade 2, first MAG-3 scan prior to 18months of age, DRF <40% and post-furosemide half-time (T1/2) <20 min. Exclusion criteria were: hydroureter, VUR, solitary kidney, duplication anomalies. Outcomes of interest were a progression of T1/2 ≥ 20 min and/or further decline in DRF >5%. Results: Of 704 patients with unilateral hydronephrosis, 91 had DRF≤40%, of which 29 (18 boys, 11 girls) met our inclusion criteria and were followed for a mean of 2.8 years (1.4 months-6.6 years). Mean age at first sonogram was 2.3 months. 2 patients had SFU grade 2, 16 had grade 3, and 9 had grade 4 hydronephrosis, and 2 unknown grade. Median half-time on initial MAG-3 scan across all patients was 10 min (3–20 min). Initial MAG3 scan was performed at a median of 2.3 months of age (0.3–17 months). 22/29 patients had >1 MAG3 scan. Of the 7 remaining, 5 were lost to follow-up and 2 demonstrated improvement in hydronephrosis. Worsening drainage occurred in 10/22(45%), median final T1/2 was 45.5 min 8 of these underwent pyeloplasty and 2 were lost to follow up. 4/22 patients (18%) had progressive decline in DRF (mean 8.3%, range 6–10%). 3/4 maintained non-obstructive drainage patterns and stable/improved hydronephrosis, and 1 underwent pyeloplasty. 13/18 remaining patients had stable DRF and 5 had improvement in DRF. 7(39%) of these underwent surgery for worsening drainage (Summary Figure). Overall, 7/29(24%) patients had sufficient resolution of hydronephrosis to be discharged from our care, 8(28%) are under continued observation, 9(31%) underwent pyeloplasty, and 5(17%) were lost to follow-up. In the observational group [median follow-up 4.5 years (3.7-6.6 years)], all 8 demonstrated improved non-obstructive drainage (T1/2 <20 minutes) and/or improvement in hydronephrosis. 4/10(40%) with DRF <35% underwent pyeloplasty versus 5/19(26%) with DRF 35-40%(p=0.67). Conclusion: Initial observational management of unilateral hydronephrosis with reduced DRF and nonobstructive drainage is recommended as most kidneys maintain nonobstructive drainage and do not demonstrate further decline in DRF. Even when DRF decreases, the majority remain non-obstructive. Worsening drainage over time more often leads to the decision for pyeloplasty rather than change in DRF. Summary Figure Summary Figure